2006
DOI: 10.18388/abp.2006_3332
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Y831C mutation detection in human DNA polymerase gamma by allelic discrimination assay.

Abstract: Many well-defined mutations in the gene for the catalytic subunit of polymerase gamma (POLG1) have been found to be associated with disease, whereas the status of several mutations remains unresolved due to the conflicting reports on their frequencies in populations of healthy individuals. Here, we have developed a highly sensitive, real-time allelic discrimination assay enabling detection of the Y831C mutation in the POLG1 gene. The Y831C mutation is present in the Polish population at a frequency of 2.25%. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Neither patient #3 nor her mother exhibited signs of Parkinsonism, features that have previously been reported with dominant expression of this variant . Moreover, it has been found at a high percentage in control populations, most notably in a Polish population (2.25%) . The recent findings of Wong et al .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Neither patient #3 nor her mother exhibited signs of Parkinsonism, features that have previously been reported with dominant expression of this variant . Moreover, it has been found at a high percentage in control populations, most notably in a Polish population (2.25%) . The recent findings of Wong et al .…”
Section: Discussionmentioning
confidence: 78%
“…27,28 Moreover, it has been found at a high percentage in control populations, most notably in a Polish population (2.25%). [29][30][31] The recent findings of Wong et al and Tang et al also indicate that p.Y831C is a neutral polymorphism even though its incidence in patients exhibiting symptoms suggestive of POLG-related diseases was high in these studies.…”
Section: Prevalence Of Polg Mutationsmentioning
confidence: 85%
“…Y831C is located very close to motif A in the polymerase region of POLG and has previously been reported in a family with PEO, peripheral neuropathy and Parkinsonism, but not in controls (Mancuso et al., ), pointing toward a pathogenic role. However, it has been found at a high percentage in control populations (Barthelemy et al., ; Stopinska et al., ; Tiangyou et al., ). The recent findings of Wong et al () and Woodbridge et al () also indicated that Y831C is a neutral polymorphism in spite of its incidence in patients exhibiting symptoms suggestive of POLG‐related diseases (Wong et al., ; Woodbridge et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…SNP rs2307441, insertion GTAG in intron 17 (rs2307433) and nucleotide variant c.2481–7C>T were genotyped using Custom TaqMan® SNP Genotyping Assay according to the manufacturer's instructions. Mutation Y831C was genotyped as described by Stopińska et al ().…”
Section: Methodsmentioning
confidence: 99%
“…Finally, Mancuso et al [ 25 ] reported a proband and her brother with the heterozygous Y831C mutation that presented with parkinsonism and PEO. However, the pathogenic role of this mutation is still unclear; indeed, although the Y831C mutation has been observed in heterozygous or compound heterozygous conditions in both infantile and late-onset cases with variable phenotypes, it has also been shown to be present at a high frequency in healthy controls [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%